Recognising information privacy: a comparative case study of legal change in late modern societies - Schneider, A (2020)
The development of privacy laws is often taken to represent a response to socio-technical changes of modern life. But why, if modern societies were confronted with innovations in information and communication technologies in roughly the same way at the same time, did legal systems develop such different approaches to information privacy?